A novel SGLT-2 score to identify HFpEF patients who may benefit from SGLT-2 inhibitors. (25th November 2020) - Binder, C; Poglitsch, M; Rettl, R.R; Dachs, T; Seirer, B; Capelle, C; Dusik, F; Duca, F; Dalos, D; Schrutka, L; Badr-Eslam, R; Bonderman, D
Abstract: Background: Established heart failure (HF) treatments have shown no effects in HF and preserved ejection fraction (HFpEF). Subgroup analyses of the HFpEF populations suggest that certain patients benefit from HF treatments. This underlines the importance of individualized therapy regimens in HFpEF. Sodium-glucose transporter 2 (SGLT-2) inhibitors are emerging as a promising treatment of HF. The mechanisms leading to improved outcomes include 1) treatment of diabetes, 2) osmodiuresis preventing volume overload, 3) enhancement of the cardio protective Angiotensin (Ang) 1–7 pathway, instead of Ang II. We aimed to characterize patients by factors which are modified by SGLT-2 inhibitors to identify individuals who may benefit from these drugs. Methods: HFpEF patients were included in a single center registry. Baseline evaluation included assessment of HbA1c, fluid status measured by body composition monitor and plasma angiotensin concentration. A "SGLT-2 score" with a maximum of 3 points was calculated using the following parameters: 1) HbA1c >6.5%, 2) overhydration, defined as a fluid overload of >1, 5L and 3) plasma renin activity (PRA) levels above the median as a parameter of over-all RAS activity. Primary outcome was defined as all-cause death or HF hospitalization. All parameters used in the "SGLT-2 score" were independently predictive for the chosen endpoint. Kaplan Meier analyses was used to show the association between the score and outcomes. Results: 90 patients were included in this registry. Median HbA1c was 6.0%, median fluid status was 1.2L and the median Ang II levels in the "high PRA-group" were 5.35.1 pmol/L. After a mean follow up time of 44.0±38.7 months, 60 patients (66.6%) reached the endpoint. Kaplan Meier analysis showed an association between SGLT-2 score and outcome (p=0.003). Conclusion: Patients with HbA1c >6.5%, overhydration and high RAS activity have poor outcomes. We propose the future use of this score to identify a subgroup of HFpEF patients who may benefit from SGLT-2 inhibitors. Funding Acknowledgement: Type of funding source: None